Rancang User Interface Media Pembelajaran Berbasis Website Untuk Mata Kuliah Animasi Komputer - Lie, Ezekiel Agatan; Mandala, Ricky; Whisly (Journal of Digital Ecosystem for Natural Sustainability, 2021)
At this time, the growth of knowledge is increasing rapidly, as well as technology. In today's world of education, learning media has become one of the best tools for carrying out the teaching and learning process. Learning Media can be an attraction for readers or college students. However, to attract the attention of readers, the user interface is the one that we can use in learning media systems, especially website-based. In this research, it’s necessary to use the Design Thinking method that focuses on human-centered design to obtain some information and data about the needs or desires of readers so we can remake the user interface according to the suggestion from the readers. The user interface of the learning media is created as a website-based for the Computer Animation courses where students are not satisfied enough with the material and learning methods. In this learning media, the knowledge of animation is available that they can see it in the form of text, images, videos, and animations.